THE INFLUENCE OF ORGANIZATIONAL STRUCTURE, WORK DISCIPLINE, COMMUNICATION, AND HUMAN RESOURCE QUALITY ON ORGANIZATIONAL PERFORMANCE AT TWWHA JO - Pujianto, Gatot; Dayona Ismail, Gurawan; Nunung Ayu Sofiati (Efi); Sudaryo, Yoyo (Pena Cendekia Insani, 2025)
This research is motivated by the importance of organizational performance in ensuring that the company can achieve strategic goals effectively and efficiently. TWWHA JO as a consortium company engaged in the construction sector faces internal challenges, such as suboptimal work coordination, varying levels of work discipline, ineffective communication between divisions, and uneven quality of human resources. The results of the study indicate that although job discipline, communication, to a certain degree, organizational structure has a positive and major impact on performance, while human resource quality has a negative and large impact on organizational performance. With a determination coefficient (R2) value of 66.2%, the four independent variables simultaneously have a significant impact on organizational performance. This indicates that organizational structure, work discipline, communication, and human resource quality account for 66.2% of the variation in organizational performance, with other factors outside the scope of this study influencing the remaining 33.8%. These findings provide implications for TWWHA JO management to pay more attention to improving the organizational structure to be more adaptive, strengthening work discipline with appropriate policies, increasing the effectiveness of cross-divisional communication, and more targeted HR quality development programs to support improving organizational performance